Sigmaxinella cearense sp. nov. from sandstone reefs off Fortaleza (Ceara State, Brazil) (Desmacellidae, Mycalina, Poecilosclerida, Demospongiae) - Salani, Sula; Lotufo, Tito M.d.c.; Hajdu, Eduardo (Zootaxa, 2006)
Sigmaxinella cearense sp. nov. is described here on the basis of a single specimen collected in 2004 at Parque Estadual Marinho da Pedra da Risca do Meio, off Fortaleza, Ceará, Brazil. This is the first record of Sigmaxinella for the Atlantic Ocean. The new species differs from the other eleven Sigmaxinella species by the absence of raphides/microxea, and is the only species with a single category of styles as megascleres (mean length 435µm, mean width 12µm), and sigmas (mean length 21µm). The new species appears to be closer to Australian species of Sigmaxinella, on the basis of overall spicule morphology (mainly dimensions and categories of megascleres). This could be suggestive of a transpacific track for the colonization of the South Atlantic, instead of the shorter Agulhas track.Key words: Sigmaxinella, taxonomy, Parque Estadual da Pedra da Risca do Meio, sponge, new species, sandstone reef, Brazil